Coating composition and cured product
By using a combination of acrylic resin, acrylate compound and quaternary ammonium compounds, the toxicity and insufficient supply of isocyanate compounds in the NCO-OH curing system were solved, and excellent substrate adhesion, chemical reagent resistance and solvent resistance were achieved. Coatings are suitable for a variety of areas with high durability and safety requirements.
Patent Information
- Application Number
- CN202380046189.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-07
- Filing Date
- 2023-06-15
- Publication Date
- 2025-01-10
AI Technical Summary
When using isocyanate compounds as curing agents, there are problems with storage stability and operability caused by toxicity, insufficient supply, and influence of air moisture. It is difficult to achieve substrate adhesion and resistance without using isocyanate systems. Coatings with excellent chemical reagent properties and solvent resistance.
By using a combination of acrylic resin, acrylate compound and a quaternary ammonium compound in a specific proportion, a coating composition having crosslinkability is prepared, and the acrylate compound therein is used as a crosslinking agent and a quaternary ammonium compound as a base catalyst to promote the promotion of The curing reaction forms a cured product with excellent substrate adhesion, chemical reagent resistance and solvent resistance.
It is achieved without the use of isocyanate system to obtain cured substances with excellent adhesion, chemical reagent resistance and solvent resistance, and improve the durability and safety of the coating. It is suitable for automotive interior and exterior installations, household appliances and Building materials and other fields.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to a coating composition and a cured product. In particular, it relates to a coating composition capable of obtaining a cured product (coating product) having excellent substrate adhesion, chemical resistance, and solvent resistance required in various fields such as automotive interior and exterior, household appliances, and coatings and film coatings for building materials, and a cured product obtained by using the coating composition. Background Art
[0002] Coating compositions used in automobiles, home appliances, building materials, etc. require various properties such as chemical resistance, scratch resistance, and substrate adhesion. As a curing form that meets these required properties, the NCO-OH curing system that reacts an isocyanate group (NCO) with a hydroxyl group (OH) is widely used.
[0003] In the NCO—OH curing system, isocyanate compounds are used as curing agents for curing agents, coatings, etc., and organic tin compounds such as dibutyltin oxide and dibutyltin dilaurate are generally used as catalysts for accelerating the curing reaction using isocyanate compounds (see Patent Document 1).
[0004] However, although organotin compounds have high catalytic performance, their toxicity has become a problem in recent years, and catalysts that can replace organotin compounds have been sought.
[0005] The NCO-OH curing system has high versatility, but on the other hand, there are problems with storage stability and workability, such as the influence of moisture in the air and a shortened usable time (pot life) after adding an isocyanate compound as a curing agent.
[0006] In addition, isocyanate compounds have problems with toxicity to the body and shortage of raw materials, and a non-NCO—OH curing system that is excellent in substrate adhesion, chemical resistance, etc. without using an isocyanate compound as a curing agent is desired.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent Application Publication No. 2004-307800 Summary of the invention
[0010] Problems to be solved by the invention
[0011] Therefore, an object of the present invention is to provide a coating composition and a cured product that can produce a cured product (coated product) having excellent substrate adhesion, chemical resistance, and solvent resistance without using an isocyanate-based curing agent.
[0012] Means for solving problems
[0013] The present inventors have conducted intensive studies and have found that a cured product (coated product) having excellent substrate adhesion, chemical resistance, and solvent resistance can be obtained by using a coating composition containing an acrylic resin obtained by blending specific monomers in a specific ratio, a cross-linkable acrylate compound, and a specific base catalyst, thereby completing the present invention.
[0014] That is, the present invention relates to the following coating composition, which contains an acrylic resin (1), an acrylate compound (2) and a quaternary ammonium compound (3),
[0015] The monomer components constituting the acrylic resin (1) include:
[0016] 5 to 50% by mass of a β-diketone group-containing monomer (A);
[0017] 0.1 to 0.8 mass % of a carboxyl group-containing monomer (B); and
[0018] 49.5 to 94.5% by mass of a monomer (C) other than the monomer (A) and the monomer (B), wherein the monomer (C) does not contain any functional group of a hydroxyl group, a nitrile group, and an amide group and has a homopolymer having a glass transition temperature of 60° C. or higher.
[0019] In the coating composition of the present invention, the acrylic resin (1) preferably has a weight average molecular weight of 3,000 to 80,000.
[0020] In the coating composition of the present invention, the acrylic resin (1) preferably has a glass transition temperature of 40 to 100°C.
[0021] The present invention relates to a cured product of the above coating composition.
[0022] Effects of the Invention
[0023] By using the coating composition of the present invention, a cured product (coating product) having excellent substrate adhesion, chemical resistance and solvent resistance can be obtained, and it can be used in fields requiring high durability and safety, such as automotive interior and exterior, household appliances, and coatings and film coatings for building materials, and is useful. DETAILED DESCRIPTION
[0024] [Acrylic resin (1)]
[0025] The coating composition of the present invention is characterized in that it contains an acrylic resin (1), which contains, as monomer components constituting the acrylic resin (1), 5 to 50% by mass of a monomer (A) containing a β-diketone group; 0.1 to 0.8% by mass of a monomer (B) containing a carboxyl group; and 49.5 to 94.5% by mass of a monomer (C) other than the monomer (A) and the monomer (B), wherein the monomer (C) does not contain any functional groups among hydroxyl groups, nitrile groups and amide groups and has a homopolymer having a glass transition temperature of 60° C. or above.
[0026] The acrylic resin (1) is useful because it contains specific monomers at specific ratios and a cured product (coating product) obtained by using the acrylic resin (1) has excellent substrate adhesion, water resistance, weather resistance, chemical resistance and solvent resistance.
[0027] [Monomer containing β-diketone group (A)]
[0028] The monomer components constituting the acrylic resin (1) contain 5 to 50% by mass of a β-diketone group-containing monomer (A) (hereinafter sometimes referred to as "monomer (A)") relative to the total amount of the monomer components, preferably 10 to 40% by mass, and more preferably 10 to 20% by mass. In the acrylic resin (1), the use of the monomer (A) within the above range optimizes the balance between cure shrinkage and crosslink density during film formation, and the resulting cured product exhibits excellent curability, and the cured product also has excellent adhesion to a substrate (substrate adhesion), which is useful. It should be noted that the monomer (A) is different from the monomers (B) to (E) described later.
[0029] As the monomer (A), any polymerizable monomer having a β-diketone group may be used without particular limitation, and examples thereof include 2-acetoacetoxyethyl (meth)acrylate, 2-acetoacetoxypropyl (meth)acrylate, and acetoacetoxybutyl (meth)acrylate, among which 2-acetoacetoxyethyl methacrylate (AAEM) is preferred. These may be used alone or in combination of two or more.
[0030] [Carboxyl group-containing monomer (B)]
[0031] The monomer components constituting the acrylic resin (1) contain 0.1 to 0.8% by mass of a carboxyl-containing monomer (B) (hereinafter sometimes referred to as "monomer (B)") relative to the total amount of the monomer components, preferably 0.1 to 0.5% by mass, and more preferably 0.1 to 0.3% by mass. In the acrylic resin (1), the monomer (B) is used within the above range, thereby taking into account the balance of compatibility with the catalyst, curability and pot life, and is useful. It should be noted that when the monomer (B) is relatively large (for example, 1.0% by mass), poor curing is likely to occur in the resulting coating composition, which is not preferred. It should be noted that the monomer (B) is different from the monomer (A) and the monomers (C) to (E) described later.
[0032] As the monomer (B), any polymerizable monomer having a carboxyl group can be used without particular limitation, and examples thereof include (meth)acrylic acid, crotonic acid, β-carboxyethyl (meth)acrylate, ω-carboxy-polycaprolactone mono(meth)acrylate, unsaturated monocarboxylic acids such as 2-(meth)acryloyloxyethyl succinate and 2-(meth)acryloyloxyethyl hexahydrophthalate, unsaturated dicarboxylic acids such as maleic acid, fumaric acid and itaconic acid, or half esters of these unsaturated dicarboxylic acids, and the like. Among them, (meth)acrylic acid is more preferred from the viewpoint of copolymerizability with other monomers. These may be used alone or in combination of two or more.
[0033] [Monomer (C) other than the above monomer (A) and the above monomer (B) which does not contain any functional group among hydroxyl group, nitrile group and amide group and has a homopolymer glass transition temperature of 60°C or higher]
[0034] The monomer components constituting the acrylic resin (1) contain 49.5 to 94.5% by mass of a monomer (C) other than the monomer (A) and the monomer (B) (hereinafter sometimes referred to as "monomer (C)") relative to the total amount of the monomer components. The monomer (C) does not contain any functional group of a hydroxyl group, a nitrile group, or an amide group and has a homopolymer glass transition temperature of 60°C or higher. The monomer (C) preferably contains 52 to 88% by mass, and more preferably contains 54 to 86% by mass. In the acrylic resin (1), when the monomer (C) is used within the above range, the glass transition temperature of the acrylic resin (1) obtained is improved, and a coating film having high durability is obtained. The cured product obtained by using the obtained coating composition has improved solvent resistance and chemical resistance, and is useful. It should be noted that the monomer (C) is different from the monomers (A), (B), the monomers (D) and (E) described later, and the like.
[0035] As the monomer (C), any polymerizable monomer other than the monomer (A) and the monomer (B) which does not contain any functional group of a hydroxyl group, a nitrile group, and an amide group and has a homopolymer having a glass transition temperature of 60° C. or higher may be used without particular limitation, and examples thereof include styrene, methyl methacrylate, ethyl methacrylate, isopropyl methacrylate, tert-butyl methacrylate, cyclohexyl methacrylate, 3,3,5-trimethylcyclohexyl methacrylate, isobornyl methacrylate, and isobornyl acrylate, among which methyl methacrylate is more preferred from the viewpoint of the polarity of the monomer. These may be used alone or in combination of two or more.
[0036] [Alkyl (meth)acrylate (D) having an alkyl group having 2 to 10 carbon atoms, the glass transition temperature of the homopolymer being lower than 60° C.]
[0037] The monomer components constituting the acrylic resin (1) may further contain an alkyl (meth)acrylate (D) having an alkyl group having 2 to 10 carbon atoms and a homopolymer glass transition temperature of less than 60°C (hereinafter sometimes referred to as "monomer (D)"). In particular, the alkyl (meth)acrylate having an alkyl group having 2 to 4 carbon atoms and a homopolymer glass transition temperature of less than 60°C may be contained from the viewpoint of the polarity of the polymer after polymerization and the solubility in a solvent. The monomer (D) is different from the monomers (A) to (C) and the monomer (E) described later.
[0038] Examples of the monomer (D) include ethyl acrylate, propyl (meth)acrylate, isopropyl acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, and isodecyl (meth)acrylate. Among them, butyl (meth)acrylate is more preferably used from the viewpoint of the polarity of the polymer after polymerization and the solubility in the solvent. These may be used alone or in combination of two or more.
[0039] The amount of the monomer (D) is preferably 15% by mass or less, more preferably 10% by mass or less, based on the total amount of monomer components constituting the acrylic resin (1).
[0040] [Other monomer components]
[0041] As monomer components constituting the acrylic resin (1), in addition to the above-mentioned monomer (A) and the like, polymerizable monomers such as hydroxyl group-containing monomers, amide group-containing monomers, amino group-containing monomers and epoxy group-containing monomers may be used as other monomer components (hereinafter sometimes referred to as "monomer (E)") as necessary.
[0042] The amount of the monomer (E) is preferably 0 to 5% by mass, more preferably 0 to 3% by mass, based on the total amount of monomer components constituting the acrylic resin (1).
[0043] The acrylic resin (1) can be obtained by appropriately combining and polymerizing the monomers (A) and the like according to desired properties. The acrylic resin (1) may include any of a random copolymer, a block copolymer, a graft copolymer, and the like.
[0044] (Aggregation Method)
[0045] As a method for polymerizing the acrylic resin (1), any appropriate method may be adopted, and examples thereof include solution polymerization, bulk polymerization, emulsion polymerization, and various radical polymerizations. Among them, solution polymerization is preferred from the viewpoint of ease of handling.
[0046] (Free Radical Polymerization Initiator)
[0047] The acrylic resin (1) may contain a radical polymerization initiator when performing radical polymerization. The radical polymerization initiator may be, for example, a thermal polymerization initiator that generates radicals when heated. These may be used alone or in combination of two or more.
[0048] Examples of the radical polymerization initiator include peroxide radical polymerization initiators, azo radical polymerization initiators, etc. Among them, peroxide radical polymerization initiators are preferred.
[0049] Examples of the peroxide-based radical polymerization initiator include hydroperoxide compounds such as 1,1,3,3-tetramethylbutyl hydroperoxide; dialkyl peroxide compounds such as tert-butylcumyl peroxide, di-tert-butyl peroxide, di-tert-hexyl peroxide, dicumyl peroxide, 1,4-bis(1-tert-butylperoxy-1-methylethyl)benzene, and 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane; dilauroyl peroxide, didecanoyl peroxide, dicyclohexyl peroxydicarbonate, and bis(4-tert-butylcyclohexyl) peroxydicarbonate. and other diacyl peroxide compounds; tert-butyl peroxyacetate, tert-butyl peroxybenzoate, tert-butyl peroxyisopropyl monocarbonate, tert-butyl peroxy-2-ethylhexanoate, tert-hexyl peroxy-2-ethylhexanoate, tert-butyl peroxyneodecanoate, tert-hexyl peroxyisopropyl monocarbonate, tert-butyl peroxylaurate, (1,1-dimethylpropyl) 2-ethylperhexanoate, tert-butyl 2-ethylperhexanoate, tert-butyl 3,5,5-trimethylperhexanoate, tert-butyl peroxy-2-ethylhexyl monocarbonate, tert-butyl peroxymaleate and other peroxyester compounds, etc.
[0050] Examples of the azo radical polymerization initiator include azobis(4-methoxy-2,4-dimethylvaleronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylbutyronitrile), 1,1'-azobis(cyclohexane-1-carbonitrile), 1-[(1-cyano-1-methylethyl)azo]formamide, and 2-phenylazo-4-methoxy-2,4-dimethylvaleronitrile; and azobis[2-methyl-N-[1,1-bis(hydroxymethyl)-2-hydroxyethyl]propionamide], 2,2'-azobis[2-methyl-N-[1,1-bis(hydroxymethyl)-2-hydroxyethyl]propionamide]. Azoamide compounds such as bis(hydroxymethyl)ethylpropionamide, 2,2'-azobis[2-methyl-N-[2-(1-hydroxybutyl)]-propionamide], 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)-propionamide], 2,2'-azobis(2-methylpropionamide) dihydrate, 2,2'-azobis[N-(2-propenyl)-2-methylpropionamide], 2,2'-azobis(N-butyl-2-methylpropionamide), 2,2'-azobis(N-cyclohexyl-2-methylpropionamide); alkylazo compounds such as 2,2'-azobis(2,4,4-trimethylpentane) and 2,2'-azobis(2-methylpropane), etc.
[0051] Examples of commercially available products of the radical polymerization initiator include “PERBUTYL C”, “PERBUTYL A”, “PERBUTYL P”, “PERBUTYL L”, “PERBUTYL O”, “PERBUTYL ND”, “PERBUTYL Z”, “PERBUTYL I”, “PERCUMYL P”, “PERCUMYL D”, “PERHEXYL D”, “PERHEXYL A”, “PERHEXYL I”, “PERHEXYL Z”, “PERHEXYL ND”, “PERHEXYL O”, “PERHEXYL PV”, and “PERHEXYL O” manufactured by NOF Corporation.
[0052] The amount of the polymerization initiator used may be a common amount, for example, 0.3 to 15 parts by mass, preferably 0.5 to 10 parts by mass, based on 100 parts by mass of the total amount of the monomer components constituting the acrylic resin (1).
[0053] The polymerization temperature and polymerization time can be appropriately selected according to the type of monomers and polymerization initiator used. For example, the polymerization temperature can be about 80 to 130° C., and the polymerization time can be about 5 to 20 hours.
[0054] (Chain transfer agent)
[0055] In addition, various chain transfer agents (molecular weight modifiers or polymerization degree modifiers) known in the past can be used as needed during polymerization. The chain transfer agent can be selected from mercaptans such as n-lauryl mercaptan, tert-lauryl mercaptan, glycidyl mercaptan, and 2-mercaptoethanol, among which tert-lauryl mercaptan is preferably used. These can be used alone or in combination of two or more.
[0056] The amount of the chain transfer agent used may be a normal amount, and can be selected from a range of about 0.1 to 10 parts by mass based on 100 parts by mass of the total amount of the monomer components constituting the acrylic resin (1).
[0057] The weight average molecular weight (Mw) of the acrylic resin (1) is preferably 3000 to 80000, more preferably 3500 to 70000, and even more preferably 4000 to 60000. When the weight average molecular weight (Mw) is within the above range, the balance between coating film properties and workability is good, which is useful.
[0058] The glass transition temperature (Tg) of the acrylic resin (1) is preferably 40 to 100° C., more preferably 45 to 95° C., and even more preferably 50 to 90° C. When the glass transition temperature (Tg) is within the above range, the coating film has a good balance of physical properties and is useful.
[0059] [Acrylate compound (2)]
[0060] The coating composition of the present invention is characterized in that, in addition to the acrylic resin (1), it further contains an acrylate compound (2) other than the raw materials used in the acrylic resin (1). Unlike the acrylic resin (1), the acrylate compound (2) functions as a crosslinking agent (crosslinking monomer), which is important for obtaining a cured product using the coating composition. In addition, the acrylate compound (2) can be any compound having one or more (meth)acryloyl groups (having unsaturated double bonds) in one molecule, and preferably has two or more (meth)acryloyl groups in one molecule from the viewpoint of improving chemical resistance and solvent resistance.
[0061] Examples of the acrylate compound (2) include monoesters such as methyl acrylate, lauryl acrylate, stearyl acrylate, isostearyl acrylate, tetrahydrofurfuryl acrylate, (methoxyethyl) acrylate, methoxypolyethylene glycol acrylate, (2-methyl-2-ethyl-1,3-dioxolan-4-yl) acrylate, [{cyclohexaspiro-2-(1,3-dioxolan-4-yl)}methyl] acrylate, and {(3-ethyloxetan-3-yl)methyl} acrylate; ethylene glycol diacrylate, propylene glycol diacrylate, butanediol diacrylate, pentanediol diacrylate, hexanediol diacrylate, heptanediol diacrylate, octanediol diacrylate, nonanediol diacrylate, decanediol diacrylate, glycerol-1,2-diacrylate, glycerol-1,3-diacrylate, pentaerythritol diacrylate, and 2-hydroxy-methacrylate. 3-acryloxypropyl, tricyclodecane dimethanol diacrylate, dipropylene glycol diacrylate, tripropylene glycol diacrylate and other diesters; glycerol triacrylate, trimethylolpropane triacrylate, pentaerythritol triacrylate, dipentaerythritol triacrylate, ethoxylated isocyanuric acid triacrylate, ethoxylated glycerol triacrylate, ethoxylated trimethylolpropane triacrylate, pentaerythritol tetraacrylate, dipentaerythritol pentaacrylate, dipentaerythritol hexaacrylate, ditrimethylolpropane tetraacrylate, ethoxylated pentaerythritol tetraacrylate, trimethylolpropane trimethacrylate, tripentaerythritol octaacrylate, etc., wherein, from the viewpoint of taking into account the substrate adhesion and chemical resistance and solvent resistance, tricyclodecane dimethanol diacrylate, trimethylolpropane triacrylate, dipentaerythritol pentaacrylate, dipentaerythritol hexaacrylate are more preferred. They can be used alone or in combination of two or more.
[0062] (Other crosslinking agents (curing agents))
[0063] In addition to the acrylate compound (2), the coating composition may further contain other curing agents (crosslinking agents) as required. The crosslinking agent is not particularly limited, and examples thereof include epoxy crosslinking agents, oxazoline crosslinking agents, aziridine crosslinking agents, metal chelate crosslinking agents, carbodiimide crosslinking agents, etc. The crosslinking agent may be used appropriately according to the type of functional groups contained in the coating composition used. It should be noted that isocyanate crosslinking agents have problems such as shortening the usable time (applicable period) of the coating composition, and are therefore preferably not used. They may be used alone or in combination of two or more.
[0064] Regarding the amount of the acrylate compound (2) used, the molar ratio of the active proton CH in the β-diketone group-containing monomer (A) constituting the acrylic resin (1) to the unsaturated double bond C═C in the acrylate compound (2) can be selected within the range of 0.5 to 2.0, and is preferably selected within the range of 0.8 to 1.2 from the viewpoint of the balance between substrate adhesion and chemical resistance and solvent resistance.
[0065] [Quaternary ammonium compounds (3)]
[0066] The coating composition of the present invention is characterized in that it further contains a quaternary ammonium compound (3) in addition to the acrylic resin (1) and the acrylate compound (2). The quaternary ammonium compound (3) is a base catalyst, and from the viewpoint of promoting the curing reaction while heating, it plays a role as a thermal latent curing catalyst (curing accelerator), which is important for obtaining a cured product using the coating composition. In addition, as the quaternary ammonium compound (3), the number of carbon atoms in the hydrocarbon group of 3 or more bonded to the nitrogen atom in the quaternary ammonium group (cationic group) in the quaternary ammonium compound is preferably 2 or more, and the anion ionically bonded to the cationic group is preferably a hydroxide ion (OH - ), acetate ion (RCOO - ), carbonate ion (RCO3 - ), alkoxide ions (RO - ). It should be noted that the above R is preferably a hydrogen atom or an alkyl group.
[0067] Examples of the quaternary ammonium compound (3) include tetra-n-propylammonium hydroxide, tetra-n-butylammonium hydroxide, tetra-n-pentylammonium hydroxide, tetra-n-hexylammonium hydroxide, tetracyclohexylammonium hydroxide, tetrakis(trifluoromethyl)ammonium hydroxide, trimethylcyclohexylammonium hydroxide, trimethyl(trifluoromethyl)ammonium hydroxide, trimethyl-tert-butylammonium hydroxide, tetra-n-propylphosphonium hydroxide, tetra-n-butylphosphonium hydroxide, tetra-n-pentylphosphonium hydroxide, tetra-n-hexylphosphonium hydroxide, tetracyclohexylphosphonium hydroxide, Tetrakis(trifluoromethyl)phosphonium hydroxide, trimethylcyclohexylphosphonium hydroxide, trimethyl(trifluoromethyl)phosphonium hydroxide, trimethyl-tert-butylphosphonium hydroxide, tetrapropylammonium acetate, tetrabutylammonium acetate, triethylmethylammonium 2-ethylhexanoate, etc. Among them, tetrabutylammonium hydroxide, tetrabutylammonium acetate, and triethylmethylammonium 2-ethylhexanoate are preferred from the viewpoint of both curability and pot life. These may be used alone or in combination of two or more.
[0068] In addition to the quaternary ammonium compound (3), the coating composition may further contain other curing catalysts as needed. As the other curing catalysts, for example, amines such as triethylamine, N,N-benzylmethylamine, N,N-dimethylphenylamine (Japanese: N,N-ジメチルフェニルアミン), N,N-dimethylaniline (Japanese: N,N-ジメチルアニリン) and the like; imidazoles such as methylimidazole, 1,2-dimethylimidazole, 2-methyl-4-methylimidazole and the like; phosphines such as triphenylphosphine, tributylphosphine and the like. It should be noted that, from the viewpoint of the balance between the physical properties of the coating film and the pot life, it is preferred not to use coatings, inks and the like obtained by using amidines such as 1,8-diazabicyclo (5.4.0) undec-7-ene (DBU) as curing catalysts.
[0069] The amount of the quaternary ammonium compound (3) to be used can be selected from a range of about 0.1 to 6.0 parts by mass, preferably 0.3 to 3.2 parts by mass, based on 100 parts by mass of the total amount of the monomer components constituting the acrylic resin (1), from the viewpoints of substrate adhesion, chemical resistance, and solvent resistance.
[0070] (Other additives)
[0071] Other additives may also be contained as required in the above-mentioned coating composition. As the above-mentioned other additives, for example, additives such as silane coupling agent, lubricant, filler, thixotropy imparting agent, tackifier, wax, heat stabilizer, light-resistant stabilizer, fluorescent whitening agent, foaming agent, pH adjusting agent, leveling agent, anti-gelling agent, dispersion stabilizer, antioxidant, free radical scavenger, heat resistance imparting agent, inorganic filler, organic filler, plasticizer, reinforcing agent, antibacterial agent, mildewproof agent, rustproof agent, thermoplastic resin, thermosetting resin, pigment, dye, conductivity imparting agent, antistatic agent, moisture permeability improving agent, hydrophobic agent, oleophobic agent, hollow foam, compound containing crystal water, flame retardant, water absorbing agent, moisture absorbing agent, deodorant, foaming agent, defoamer, mildewproof agent, preservative, algae-proof agent, pigment dispersant, anti-blocking agent, hydrolysis-proof agent etc. may be used. The amount of these additives is not particularly limited and can be appropriately selected.
[0072] (Solvent)
[0073] In the above-mentioned coating composition, a solvent can be used as needed. As the above-mentioned solvent, for example, acetone, diethyl ketone, methyl ethyl ketone, methyl isobutyl ketone, diethyl ether, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, ethylene glycol dibutyl ether, tetrahydrofuran, dioxane, ethyl acetate, butyl acetate, isobutyl acetate, propyl acetate, n-pentane, n-hexane, cyclohexane, n-heptane, benzene, toluene, xylene, carbon tetrachloride, methylene chloride, chloroform, trichloroethane, dimethylformamide, N-methylpyrrolidone, acetonitrile, diacetone alcohol, n-butanol, propylene glycol monomethyl ether acetate, etc. can be used. The amount of these solvents is not particularly limited and can be appropriately selected.
[0074] [Coating composition]
[0075] The coating composition of the present invention relates to the following coating composition, which contains an acrylic resin (1), an acrylate compound (2) and a quaternary ammonium compound (3), and contains, as monomer components constituting the acrylic resin (1), 5 to 50% by mass of a β-diketone group-containing monomer (A); 0.1 to 0.8% by mass of a carboxyl group-containing monomer (B); and 49.5 to 94.5% by mass of a monomer (C) other than the monomer (A) and the monomer (B), wherein the monomer (C) does not contain any functional group among hydroxyl group, nitrile group and amide group and has a homopolymer having a glass transition temperature of 60° C. or above.
[0076] The coating composition has thermal latency and reacts rapidly by heating, so the composition (solution) has a long pot life, excellent storage stability and handleability, and the cured product (coating) obtained by the coating composition has excellent substrate adhesion, chemical resistance and solvent resistance, and is useful.
[0077] The method for preparing the coating composition is not particularly limited and can be prepared by a known method. For example, the coating composition can be prepared by uniformly mixing the components such as the acrylic resin (1). More specifically, the following method can be cited: a solvent is added to the acrylic resin (1) and the acrylate compound (2), the viscosity is adjusted, and a quaternary ammonium compound (3) as an alkaline catalyst is added thereto to prepare a coating composition (solution). In this method, an alkaline catalyst is added after the viscosity is adjusted, thereby avoiding partial insolubility of the alkaline catalyst and local high concentration, which is useful. In addition, this method can improve the pot life of the coating composition (solution), which is effective for coating properties, etc.
[0078] [cured material]
[0079] The present invention relates to a cured product of the coating composition. The cured product is a cured coating film (film) obtained by a crosslinking reaction of the coating composition, and is a useful cured product (coating) having excellent substrate adhesion, chemical resistance, and solvent resistance.
[0080] The solidified product (coated product) can be formed by applying the coating composition on the surface of a substrate and drying it. As a method for forming the solidified product (coated product), for example, a method can be mentioned in which the coating composition is uniformly applied on the surface of the substrate by other known methods such as a roller method, a spray method, an applicator, a rod coater, a brush, and then cured at room temperature or under heating. In the case where the coating composition contains an organic solvent as a solvent, it is preferably heated and dried using a heating roller, hot air, a hot plate, etc. after the coating.
[0081] In addition, regarding the above-mentioned curing, for example, in the case of forming a coating film (film) cured by the crosslinking reaction of the above-mentioned coating composition, from the viewpoint of curability, it is preferably heated at 40 to 120° C., and more preferably heated at 60 to 90° C. In addition, as for other curing, for example, it can be performed by heating (for example, 50 to 120° C.) under pressure (for example, 1 to 5 MPa) or light irradiation to perform free radical polymerization. In such a case, the above-mentioned known crosslinking agents (thermosetting agents, photocuring agents) and the like may also be used in combination.
[0082] [use]
[0083] The coating composition of the present invention can obtain a cured product (coating) having excellent substrate adhesion, chemical resistance and solvent resistance, and can therefore be used in fields requiring high durability and safety, such as automotive interior and exterior, home appliances, and paints and film coatings for building materials.
[0084] Example
[0085] Hereinafter, the present invention will be described in more detail with reference to Examples. However, the present invention should not be construed as being limited to the following Examples unless it exceeds the gist of the present invention.
[0086] (Production Example 1)
[0087] 390.6 parts by mass of butyl acetate were added to a flask equipped with a condenser, a thermometer, a dropping funnel, and a stirrer, and the internal temperature was raised to 110°C.
[0088] Next, a mixture of 392.6 parts by mass of methyl methacrylate, 60.5 parts by mass of butyl acrylate, 50.4 parts by mass of 2-acetoacetoxyethyl methacrylate, 0.5 parts by mass of methacrylic acid, 98.9 parts by mass of n-butyl acetate (Japanese: n-acetic acid ブチル) and 5.0 parts by mass of PERBUTYL O (made by NOF Corporation, tert-butyl peroxy-2-ethylhexanoate) was added dropwise over 5 hours. One hour after the addition, a mixture of 3.9 parts by mass of n-butyl acetate and 0.5 parts by mass of PERBUTYL O was added. Then, the polymerization reaction was carried out for 17 hours while maintaining the internal temperature at 110°C. Next, butyl acetate was added to obtain the target resin with a non-volatile component of 50% by mass. The weight average molecular weight (Mw) of the above resin is 32,000.
[0089] (Production Examples 2 to 14)
[0090] The resins of Production Examples 2 to 14 were prepared according to the formulations shown in Table 1 by the same procedure as in Production Example 1.
[0091] (Examples 1 to 13 and Comparative Examples 1 to 8)
[0092] (Coating film preparation method: non-NCO-OH curing system)
[0093] The resins obtained in Production Examples 1 to 14 (β-diketone group-containing acrylic resins) were blended with a polyfunctional acrylate (acrylate compound), and a mixed solvent of butyl acetate / isobutyl acetate / n-butyl alcohol / propylene glycol monomethyl ether acetate (30 / 30 / 30 / 10 (mass ratio)) was used as a solvent. The viscosity was adjusted to about 10 seconds using an NK-2 Iwata viscosity cup (manufactured by ANEST IWATA Co., Ltd.).
[0094] Next, a quaternary ammonium salt (quaternary ammonium compound) as an alkaline catalyst was added to prepare a coating composition (solution), which was then sprayed onto a substrate (ABS: acrylonitrile-butadiene-styrene copolymer and PC: polycarbonate). The coating was then left for 10 minutes, dried at 80°C for 1 hour, and left to stand at room temperature (about 23°C) for about 7 days to form a coating film (film thickness: 20 to 30 μm (after drying)) on the substrate.
[0095] (Comparative Examples 7 and 8)
[0096] (Coating film preparation method: NCO-OH curing system)
[0097] The resin (hydroxyl-containing acrylic resin) obtained in Production Examples 13 and 14, a polyisocyanate (Sumidur N-3300 manufactured by Sumika Covestro Urethane Co., Ltd.) as a curing agent, and a catalyst (dibutyltin dilaurate) were blended, and a mixed solvent of diacetone alcohol / isobutyl acetate / ethyl acetate / butyl acetate (30 / 30 / 30 / 10) (mass ratio) was used as a solvent. The viscosity was adjusted to about 10 seconds using an NK-2 Iwata viscosity cup (manufactured by ANEST IWATA Co., Ltd.), thereby obtaining a coating composition (solution).
[0098] Next, the coating composition (solution) was spray-coated on the substrate (ABS and PC). Then, it was left for 10 minutes, dried at 80°C for 1 hour, and further left at room temperature (about 23°C) for about 7 days to form a coating film (film thickness: 20 to 30 μm (after drying)) on the substrate.
[0099] (GPC determination)
[0100] The weight average molecular weight (Mw) of the resin obtained in the above production example was measured under the following GPC measurement conditions.
[0101] [GPC measurement conditions]
[0102] Measuring device: High-speed GPC device (Tosoh Corporation "HLC-8220GPC")
[0103] Column: The following columns manufactured by Tosoh Corporation were connected in series and used.
[0104] "TSKgel G5000" (7.8mm I.D. × 30cm) × 1 piece
[0105] "TSKgel G4000" (7.8mm I.D. × 30cm) × 1 piece
[0106] "TSKgel G3000" (7.8mm I.D. × 30cm) × 1 piece
[0107] "TSKgel G2000" (7.8mm I.D. × 30cm) × 1 piece
[0108] Detector: RI (differential refractometer)
[0109] Column temperature: 40°C
[0110] Eluent: Tetrahydrofuran (THF)
[0111] Flow rate: 1.0mL / min
[0112] Injection volume: 100 μL (tetrahydrofuran solution with a sample concentration of 4 mg / mL)
[0113] Standard sample: The following monodisperse polystyrene was used to prepare a calibration curve.
[0114] [Monodisperse polystyrene]
[0115] "TSKgel Standard Polystyrene A-500" manufactured by Tosoh Corporation
[0116] "TSKgel Standard Polystyrene A-1000" manufactured by Tosoh Corporation
[0117] "TSKgel Standard Polystyrene A-2500" manufactured by Tosoh Corporation
[0118] "TSKgel Standard Polystyrene A-5000" manufactured by Tosoh Corporation
[0119] "TSKgel Standard Polystyrene F-1" manufactured by Tosoh Corporation
[0120] "TSKgel Standard Polystyrene F-2" manufactured by Tosoh Corporation
[0121] "TSKgel Standard Polystyrene F-4" manufactured by Tosoh Corporation
[0122] "TSKgel Standard Polystyrene F-10" manufactured by Tosoh Corporation
[0123] "TSKgel Standard Polystyrene F-20" manufactured by Tosoh Corporation
[0124] "TSKgel Standard Polystyrene F-40" manufactured by Tosoh Corporation
[0125] "TSKgel Standard Polystyrene F-80" manufactured by Tosoh Corporation
[0126] "TSKgel Standard Polystyrene F-128" manufactured by Tosoh Corporation
[0127] "TSKgel Standard Polystyrene F-288" manufactured by Tosoh Corporation
[0128] "TSKgel Standard Polystyrene F-550" manufactured by Tosoh Corporation
[0129] (Glass transition temperature (Tg))
[0130] Regarding the glass transition temperature calculated by the FOX equation (hereinafter referred to as "design Tg"), the glass transition temperature (design Tg) of the resin (acrylic resin (1)) obtained in the above production example is preferably in the range of 40 to 100°C from the perspective of improving the sunscreen resistance, solvent resistance and water resistance of the obtained coating film.
[0131] It should be noted that in the present invention, the glass transition temperature calculated according to the FOX formula refers to the temperature calculated according to the FOX formula: 1 / Tg=W1 / Tg1+W2 / Tg2+···(Tg: glass transition temperature to be calculated, W1: weight fraction of component 1, Tg1: glass transition temperature of the homopolymer of component 1).
[0132] As the glass transition temperature of the homopolymer of each component, the value described in Polymer Handbook (4th Edition) by J. Brandrup, EH Immergut, EA Grulke (Wiley Interscience) or the actual value measured by differential scanning calorimetry (DSC) after synthesizing the homopolymer was used.
[0133] (Applicable period)
[0134] The coating composition (solution) obtained as described above was stored at 23° C., and the viscosity was measured at each elapsed time using an NK-2 Iwata viscosity cup (manufactured by ANESTIWATA Corporation).
[0135] Note that an evaluation of A or B is considered to be at a level that poses no practical problem (A is the best evaluation).
[0136] (Evaluation criteria)
[0137] A: After 24 hours, the fluidity is less than 2 times of the initial viscosity.
[0138] B: After 24 hours, there is fluidity, but the viscosity is more than 2 times and less than 4 times the initial viscosity.
[0139] C: No liquidity for more than 10 hours and less than 24 hours
[0140] D: No liquidity within 10 hours and beyond 0 hours
[0141] (Substrate adhesion test)
[0142] The coating films obtained on the substrates (ABS and PC) as described above were subjected to a cross-cut test (1 mm, 100 squares, 4 directions) in accordance with JIS K 5600-5-6 to visually check the adhesion of the coating films to the substrates (ABS and PC).
[0143] In addition, if the evaluation is 5B, it is judged that it is a level with no problem in practical use (5B is the best evaluation).
[0144] (Evaluation criteria)
[0145] 5B: No defects
[0146] 4B: The defect is within 5%
[0147] 3B: The defect area is more than 5% and less than 15%
[0148] 2B: The defect area is more than 15% and less than 35%
[0149] 1B: The defect area is more than 35% and less than 65%
[0150] 0B: The missing area exceeds 65%
[0151] (Water resistance test)
[0152] The coating films obtained on the substrates (ABS and PC) as described above were immersed in water (tap water) heated to 40° C. for 240 hours, and a cross-cut test (1 mm, 100 squares, 4 directions) was performed in accordance with JIS K 5600-5-6 to visually evaluate the adhesion of the coating films to the substrates (ABS and PC).
[0153] In addition, if the evaluation is 5B, it is judged that it is a level with no problem in practical use (5B is the best evaluation).
[0154] (Evaluation criteria)
[0155] 5B: No defects
[0156] 4B: The defect is within 5%
[0157] 3B: The defect area is more than 5% and less than 15%
[0158] 2B: The defect area is more than 15% and less than 35%
[0159] 1B: The defect area is more than 35% and less than 65%
[0160] 0B: The missing area exceeds 65%
[0161] (Sunscreen test)
[0162] The evaluation test was conducted using a sunscreen ("Coppertone SPORT UltraSweatproof SPF30" manufactured by SSL Healthcare Japan Co., Ltd.).
[0163] The coating film obtained on the substrate (ABS) having the coating film formed as described above was cut into a size of 50 mm×70 mm, and the sunscreen (0.5 g / 100 cm 2 ). Then, it was dried at 55°C for 4 hours. After drying, the sunscreen was washed with a neutral detergent (manufactured by Kao Corporation, trade name "Cucute"), and the coating film appearance was visually evaluated according to the following criteria.
[0164] Note that an evaluation of A or B is considered to be at a level that does not cause any practical problems (A is the best evaluation).
[0165] (Evaluation criteria)
[0166] A: No trace left
[0167] B: Some traces of the coating remain
[0168] C: There are traces of residual paint on the entire film
[0169] D: Sunscreen has not come off
[0170] (Ethanol resistance test)
[0171] A felt (manufactured by VALQUA Co., Ltd., width 10 mm × height 10 mm × depth 40 mm) containing ethanol (grade 1 reagent 95% or more) was pressed against the coating film obtained on the substrate (ABS) as described above, and a friction test was performed with a reciprocating upper limit of 500 times while applying a load of 1 kg. The state of the coating film after friction was visually observed, and the number of times until the base of the ABS substrate was seen was evaluated according to the following criteria.
[0172] Note that an evaluation of A or B is considered to be at a level that does not cause any practical problems (A is the best evaluation).
[0173] (Evaluation criteria)
[0174] A: More than 500 times
[0175] B: More than 350 times and less than 500 times
[0176] C: More than 150 times and less than 350 times
[0177] D: Less than 150 times
[0178] [Table 1]
[0179]
[0180] Hereinafter, the abbreviations in Tables 2 and 3 will be described.
[0181] DPHA: Made by Toagosei Co., Ltd., dipentaerythritol pentaacrylate / dipentaerythritol hexaacrylate (trade name: ARONIX M-402)
[0182] TMPTA: Trimethylolpropane triacrylate (trade name: Miramar M300) manufactured by MIWON
[0183] A-DCP: Tricyclodecane dimethanol diacrylate (trade name: NK EsterA-DCP) manufactured by Shin Nakamura Chemical Co., Ltd.
[0184] N-3300: Sumidur N-3300, manufactured by Sumika Covestro Urethane Co., Ltd., urate of hexamethylene diisocyanate (trade name: Sumidur N-3300)
[0185] tBAOH: Tetrabutylammonium hydroxide manufactured by Tokyo Chemical Industry Co., Ltd.
[0186] tBAAc: Tetrabutylammonium acetate manufactured by Tokyo Chemical Industry Co., Ltd.
[0187] U-CAT 18X: Triethymethylammonium 2-ethylhexanoate (trade name: U-CAT18X) manufactured by San-Apro Co., Ltd.
[0188] DBU: manufactured by Kanto Chemical Co., Ltd., 1,8-diazabicyclo[5.4.0]undec-7-ene
[0189] DBTDL: Dibutyltin dilaurate, manufactured by Nitto Kasei Co., Ltd.
[0190] ABS (sheet): manufactured by Showa Denko Materials Co., Ltd., acrylonitrile-butadiene-styrene copolymer (trade name: KOBE POLYSHEET ABS-BKWB)
[0191] PC (board): manufactured by TAKIRON, polycarbonate (trade name: PC1600)
[0192] [Table 2]
[0193]
[0194] [Table 3]
[0195]
[0196] Based on the above evaluation results, it can be confirmed that in all examples, the application period of the obtained coating composition (solution) is not a problem in practical use and the storage stability is excellent. The coating (coating film) obtained using the above coating composition is also excellent in substrate adhesion, water resistance, sunscreen (chemical resistance) and ethanol resistance (solvent resistance).
[0197] On the other hand, according to the above evaluation results, in Comparative Examples 1 to 4, 7 and 8, since the resins in which the desired monomer components were not used in the desired mixing ratio were used, all the properties could not be satisfied at the level that would not cause any practical problems. In addition, in Comparative Examples 5 to 8, since no quaternary ammonium compound was used as a catalyst, the pot life was short and all other properties could not be satisfied.
Claims
1. A coating composition comprising an acrylic resin (1), an acrylate compound (2) and a quaternary ammonium compound (3), The monomer components constituting the acrylic resin (1) include: 5% to 50% by mass of a β-diketone group-containing monomer (A); 0.1% to 0.8% by mass of a carboxyl group-containing monomer (B); and 49.5% to 94.5% by mass of a monomer (C) other than the monomer (A) and the monomer (B), wherein the monomer (C) does not contain any functional group of a hydroxyl group, a nitrile group, and an amide group and has a homopolymer having a glass transition temperature of 60° C. or higher.
2. The coating composition according to claim 1, wherein The weight average molecular weight of the acrylic resin (1) is 3,000 to 80,000.
3. The coating composition according to claim 1, wherein The acrylic resin (1) has a glass transition temperature of 40°C to 100°C. 4 . A cured product, which is a cured product of the coating composition according to claim 1 .
Citation Information
Patent Citations
Cationic electrodeposition coating composition, method of managing electrodeposition bath, and electrodeposition coating system
JP2004307800A
Method for reacting two components, compositions, coating compositions and uses thereof
EP0326723A1
Storage stable curable composition
US20060094804A1